Wide spectral response radiation-resistant optical fiber image transmission array and its preparation method and application
By preparing high transmittance and radiation resistance mandrel glass and leather tube glass, and using specific drawing and molding processes, the problem of fiber image transmission arrays being difficult to meet the wide spectrum high transmittance and radiation resistance at the same time in the radial irradiation environment, achieving the requirements of long-distance detection and long service life in the aerospace field.
Patent Information
- Application Number
- CN202411946347.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
The existing fiber optic image transmission arrays are difficult to meet the wide spectrum high transmittance and radiation resistance at the same time in the radial irradiation environment, which makes it difficult to achieve long-distance detection and long service life in the aerospace field.
By preparing mandrel glass and leather tube glass, it ensures that it has high transmittance in a specific wavelength range and maintains a low transmittance attenuation at high irradiation doses. The specific steps include placing the leather tube sleeve on the core rod, drawing monofilament and multifilament, then heating under vacuum and cleaning with oxygen, and finally isostatic molding through a gas melting mold.
The fiber image transmission array has achieved high transmittance in the wavelength range of 330-2000 nm and a low transmittance attenuation rate of 500 hours under 6.4kGy irradiation dose, meeting the requirements of long-distance detection and long service life in the aerospace field.
Smart Images

Figure BDA0005213745510000181 
Figure BDA0005213745510000191 
Figure BDA0005213745510000201
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of optical fiber manufacturing, and in particular to a wide spectrum response radiation-resistant optical fiber image transmission array and a preparation method and application thereof. Background Art
[0002] The fiber optic image transmission array is composed of tens of millions of micron-level optical fibers tightly and regularly arranged and fused together. It can transmit images with high fidelity and has the characteristics of zero optical thickness, large numerical aperture, high resolution, and strong light collection ability. It includes optical fiber panels, fiber optic image invertors, fiber optic light cones, fiber optic image transmission bundles, etc. It can be used in windows, optical coupling and display materials of photoelectric detection devices such as low-light level image intensifiers, photomultiplier tubes, X-ray image intensifiers, star sensors, and high-end radiation medical equipment. It is a high-tech and cutting-edge product in the optoelectronics industry.
[0003] The optical fiber image transmission array uses a core rod glass with a high refractive index and a skin tube glass tube with a low refractive index to arrange the plates by combining the rod and the tube with drawn single wires; the absorbent glass is drawn into wires and inserted into the arranged single wires. The absorbent glass mainly absorbs stray light; it is then bundled into a composite rod and subjected to wire drawing, plate arrangement, hot melt pressing to form a blank plate section, and then precision deep processing. It is mainly used to achieve high-definition image transmission, which solves the problem of low resolution and poor clarity of the system's field image, and improves the imaging clarity.
[0004] At present, fiber optic imaging arrays are used for long-distance detection in radiation-irradiated environments such as space. The fiber optic imaging array is required to have a wide spectrum and high transmittance to obtain a longer detection distance, and it is also required to be able to withstand radiation. It is difficult to meet both requirements at the same time. Summary of the invention
[0005] The main purpose of the present invention is to provide a wide spectrum response radiation-resistant optical fiber image transmission array and its preparation method and application. The technical problem to be solved is how to prepare a wide spectrum response radiation-resistant optical fiber image transmission array so that its spectral transmittance in the wavelength range of 330-2000nm is ≥60% at a thickness of 100mm; after irradiation for 500h at a 6.4kGy irradiation dose, the transmittance attenuation rate at 350nm is ≤5%; and it has excellent fixed pattern noise performance, and there is no obvious multifilament boundary when observed under a 10x microscope, so it can meet the requirements of long-distance detection and long service life in radiation irradiation environments such as the aerospace field, and is therefore more suitable for practical use.
[0006] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. According to a method for preparing a wide spectrum response radiation-resistant optical fiber image transmission array proposed by the present invention, the method comprises the following steps:
[0007] S11: putting a leather tube on a core rod to draw a single wire; arranging the single wire into a rod, drawing a multi-filament twice to obtain a secondary multi-filament; at a thickness of 100 mm, in a wavelength range of 330 to 2000 nm, the spectral transmittance of the core rod glass is ≥65%, and the spectral transmittance of the leather tube glass is ≥75%; irradiating for 500 hours at a 6.4 kGy irradiation dose, at 350 nm, the transmittance attenuation rate of the core rod glass and the leather tube glass is ≤3%; the refractive index of the core rod glass is ≥1.8; the refractive index of the leather tube glass is ≤1.5;
[0008] S12: arranging the secondary multifilaments in a precisely shaped glass tube and heating them under vacuum; introducing oxygen into the glass tube to clean the secondary multifilaments; and then sealing the glass tube under vacuum;
[0009] S13: placing the sealed glass tube in a gas melting and pressing mold, and isostatically pressing the mold under heating conditions to obtain a fiber optic imaging array blank;
[0010] S14 performs fine processing on the blank to obtain a wide spectral response radiation-resistant optical fiber image transmission array.
[0011] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0012] Preferably, in the above-mentioned preparation method, the difference between the thermal expansion coefficient of the core rod glass and the thermal expansion coefficient of the skin tube glass is 1×10 -7 / ℃~10×10 -7 / ℃; the softening temperature of the core rod glass minus the softening temperature of the skin tube glass is 10~25℃; the refractive index of the core rod glass minus the refractive index of the skin tube glass is greater than 0.3; both the core rod glass and the skin tube glass remain chemically stable at 810℃; the inner diameter of the skin tube glass minus the outer diameter of the core rod glass is 0.4~0.6mm.
[0013] Preferably, in the above-mentioned preparation method, the heating control temperature in step S12 is 450-480°C; the cleaning is carried out at a vacuum pressure of ≤10 -6 Pa, oxygen is introduced into the glass tube, the temperature is kept, and then the oxygen is extracted; the cleaning times are 2 to 3 times; after cleaning, helium is introduced into the glass tube for replacement, and then the helium is extracted and vacuumized to make the vacuum pressure of the glass tube ≤10 -6 Pa.
[0014] Preferably, in the aforementioned preparation method, the heating control temperature in step S13 is 600-650° C.; and the isostatic pressing is maintained in a nitrogen atmosphere of 10-13 MPa for 20-40 minutes.
[0015] Preferably, in the aforementioned preparation method, when the primary multifilament rods are arranged, triangular light-absorbing wires are inserted into the gaps of the primary multifilaments; the edges and corners of the triangular light-absorbing wires are all chamfered structures; and the secondary multifilaments are drawn using a high-precision lossless wire drawing machine.
[0016] Preferably, in the aforementioned preparation method, the preparation method of the mandrel and the leather tube is as follows:
[0017] S61 raw materials are measured and mixed to obtain a core rod mixture and a leather tube mixture;
[0018] S62 melts the core rod mixture and the skin tube mixture respectively, clarifies and stirs, discharges, casts and anneals to obtain the core rod or skin tube; the core rod mixture comprises, by weight percentage, 10-15% quartz sand, 20-30% boric acid, 19.5-30% lanthanum oxide, 1.1-10% zinc oxide, 1.1-10% niobium oxide, 10.1-20% barium carbonate, 0-3% hafnium oxide, 5.1-10% tantalum oxide, 1.1-7% yttrium oxide, 0-5% strontium carbonate, 0.5-7% aluminum oxide, 0-5% sodium carbonate and 0.05-2% cerium oxide; the skin tube mixture comprises, by weight percentage, 60-75% quartz sand, 1.5-15% boric acid, 19.5-30% lanthanum oxide, 1.1-10% zinc oxide, 1.1-10% niobium oxide, 10.1-20% barium carbonate, 0-3% hafnium oxide, 5.1-10% tantalum oxide, 1.1-7% yttrium oxide, 0-5% strontium carbonate, 0.5-7% aluminum oxide, 0-5% sodium carbonate and 0.05-2% cerium oxide. Aluminum 1-5%, sodium carbonate 1-10%, potassium bifluoride 1-8%, calcium fluoride 1-8%, basic magnesium carbonate 0-5%, lithium carbonate 0-8%, zinc oxide 0-5%, cerium oxide 0-2%; in the two mixtures, the total content of impurities Fe, Cu and Mn is ≤3ppm; the total content of impurities Nd, Pr, U, Er, Eu, Tb, Dy is ≤2ppm; the instruments for preparing and melting the core rod mixture are all made of non-metallic alkali-resistant materials; the instruments for preparing and melting the leather tube mixture are all made of non-metallic materials; oxygen is introduced into the glass liquid during the melting, clarifying and stirring steps; the material of the melting furnace used for melting and clarifying is refractory material, and its heavy metal content is ≤5ppm.
[0019] Preferably, in the aforementioned preparation method, the container for melting the core rod mixture is a crucible made of magnesium oxide; the container for melting the tube mixture is a crucible made of quartz, and the surface of the crucible is provided with a silicon oxide coating; the refractory material is a corrosion-resistant and high-temperature resistant material, and its temperature resistance is ≥1700°C; the melting furnace for melting the core rod mixture is dedicated to the preparation of the core rod glass; or, the melting furnace for melting the tube mixture is dedicated to the preparation of the tube glass.
[0020] Preferably, in the aforementioned preparation method, when preparing the core rod, the flow rate of oxygen introduced into the glass liquid is 0.1-0.3 mol / L / min; or, when preparing the leather tube, the flow rate of oxygen introduced into the glass liquid is 0.04-0.18 mol / L / min.
[0021] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. According to the wide spectrum response radiation-resistant optical fiber image transmission array proposed by the present invention, the unit fiber diameter is 3-6 μm; the optical fiber image transmission array has a spectral transmittance of ≥60% in the wavelength range of 330-2000 nm at a thickness of 100 mm; the transmittance attenuation rate at 350 nm is ≤5% when irradiated for 500 h at a 6.4 kGy irradiation dose; and there is no obvious multifilament boundary when observed under a 10x microscope.
[0022] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions: According to the present invention, a wide spectrum response radiation-resistant optical fiber image transmission array is applied in wide spectrum detection in high radiation environment in the aerospace field.
[0023] By means of the above technical solution, the wide spectrum response radiation-resistant optical fiber image transmission array and its preparation method and application proposed by the present invention have at least the following advantages:
[0024] The wide spectrum response radiation-resistant optical fiber image transmission array proposed in the present invention and its preparation method and application are as follows: a core rod made of wide spectrum response radiation-resistant core rod glass is made into a core rod, a skin tube made of wide spectrum response radiation-resistant skin tube glass is made into a skin tube, and the skin tube is sleeved on the outside of the core rod to form a rod tube; the rod tube is drawn from single filaments, the single filament rods are arranged into primary multifilament rods and drawn into primary multifilaments, and the primary multifilament rods are arranged into secondary multifilament rods and drawn into secondary multifilaments; the secondary multifilaments are arranged in a precisely shaped glass tube, heated under vacuum and oxygen is introduced into the glass tube to clean the secondary multifilaments; under the heating condition, the fiber surface activity of the secondary multifilaments is relatively large, but the glass on the fiber surface has no fluidity. The present invention can ensure that all pollutants on the fiber surface are ablated cleanly by keeping the secondary multifilaments warm in an oxygen environment, and can also complete the repair of oxygen vacancies in the fiber surface structure, so that the cleaned secondary multifilaments The surface of the silk fiber is clean and dense, which provides a guarantee for the optical fiber to have good radiation resistance. In order to keep the surface of the secondary multifilament fiber in a clean state, the present invention seals the glass tube under a high vacuum state after cleaning, so that the secondary multifilament fiber is in a closed space to avoid secondary contamination. Then, by placing the closed glass tube in a gas-melting pressing mold and isostatically pressing it under heating conditions, this gas-melting pressing method can eliminate the phenomenon of uneven force on the fiber during the mechanical molding process, thereby preventing uneven elongation of the fiber during the hot pressing process, resulting in uneven fiber structure of the optical fiber imaging array, resulting in microstructural defects in the optical fiber imaging array, so that the obtained optical fiber imaging array blank has a more uniform microstructure, avoiding or reducing microstructural defects in the optical fiber imaging array, and further providing a guarantee for the optical fiber to have good radiation resistance.The technical scheme of the present invention regulates the performance of core glass and skin glass so that at a thickness of 100 mm and in a wavelength range of 330 to 2000 nm, the spectral transmittance of the core rod glass is ≥65%, and the spectral transmittance of the skin tube glass is ≥75%; after irradiation for 500 hours at a 6.4 kGy irradiation dose, the transmittance attenuation rates of the core rod glass and the skin tube glass at 350 nm are both ≤3%; thereby, the core rod glass and the skin tube glass themselves have excellent wide spectrum response and radiation resistance performance, and further, by strictly controlling the preparation process of the optical fiber imaging array, the introduction of pollutants in the preparation process is avoided or reduced, and the inevitable pollutants are ablated by keeping the secondary multifilaments warm in an oxygen atmosphere, and the oxygen vacancies on the surface of the secondary multifilaments are repaired; by sealing the cleaned and repaired secondary multifilaments in a glass tube under vacuum conditions, the clean secondary multifilaments are avoided from being contaminated by secondary contamination; and finally, the sealed glass tube is melt-pressed into Isostatic pressing under heating conditions in a mold makes its microstructure more uniform and has fewer microstructural defects, which reduces its ability to form color centers in a radiation environment, thereby enhancing its radiation resistance. Reducing defects in the optical fiber imaging array is also beneficial to improving its ultraviolet transmission performance, so that the wide spectrum response and radiation resistance of the core rod glass and the leather tube glass can be inherited to the optical fiber imaging array, thereby ensuring that the optical fiber imaging array prepared by the present invention has excellent comprehensive performance. When the unit fiber diameter is 3 to 6 μm, at a thickness of 100 mm, the spectral transmittance is ≥60% in the wavelength range of 330-2000 nm; after irradiation for 500 hours at a irradiation dose of 6.4 kGy, the transmittance attenuation rate at 350 nm is ≤5%; and it has excellent fixed pattern noise performance, and there is no obvious multifilament boundary when observed under a 10x microscope, which can meet the requirements of long-distance detection and long service life in ray irradiation environments such as the aerospace field.
[0025] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION
[0026] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a wide spectrum response radiation-resistant optical fiber image transmission array and its preparation method and application according to the present invention, its specific implementation method, structure, characteristics and effects in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0027] The present invention provides a method for preparing a wide spectral response radiation-resistant optical fiber image transmission array, which comprises the following steps:
[0028] The first step is to prepare a core rod and a skin tube. In the present invention, both the core rod glass and the skin tube glass are glasses with wide spectral response and radiation resistance, and their performance meets the following requirements: at a thickness of 100 mm, in a wavelength range of 330 to 2000 nm, the spectral transmittance of the core rod glass is ≥65%, and the spectral transmittance of the skin tube glass is ≥75%; at a 6.4 kGy irradiation dose for 500 hours, the transmittance attenuation rate of the core rod glass and the skin tube glass at 350 nm is ≤3%.
[0029] In a specific embodiment of the present invention, the method for preparing the core rod and the leather tube is as follows: raw materials are weighed and mixed to obtain a core rod mixture and a leather tube mixture; the core rod mixture and the leather tube mixture are melted, clarified and stirred, discharged, cast and annealed to obtain a core rod or a leather tube. The specific description is as follows:
[0030] In some specific embodiments of the present invention, the core rod mixture includes, by mass percentage, 10-15% quartz sand, 20-30% boric acid, 19.5-30% lanthanum oxide, 1.1-10% zinc oxide, 1.1-10% niobium oxide, 10.1-20% barium carbonate, 0-3% hafnium oxide, 5.1-10% tantalum oxide, 1.1-7% yttrium oxide, 0-5% strontium carbonate, 0.5-7% aluminum oxide, 0-5% sodium carbonate, and 0.05-2% cerium oxide, wherein the total content of impurities Fe, Cu and Mn is ≤3ppm; the total content of impurities Nd, Pr, U, Er, Eu, Tb, and Dy is ≤2ppm. The core rod mixture is melted, clarified, stirred, formed and annealed to obtain a core rod; each component in the core rod exists in the form of oxides, that is, it contains SiO2, B2O3, La2O3, ZnO, Nb2O5, BaO, HfO2, Ta2O5, Y2O3, SrO, Al2O3, Na2O, and CeO2.
[0031] In the core rod glass, SiO2 is introduced in the form of quartz sand, which is the main body of the glass skeleton and the main component of the glass skeleton. In the core rod glass, the weight percentage of the quartz sand raw material is 10-15%. When the quartz sand raw material content is less than 10%, it is difficult to obtain a glass with a high refractive index, and the chemical resistance of the glass will also be reduced; when the quartz sand raw material content is higher than 15%, the high-temperature viscosity of the glass will increase, resulting in an excessively high glass melting temperature, and the thermal expansion coefficient of the glass will also be reduced.
[0032] B2O3 is introduced in the form of boric acid, which is an oxide for glass formation and also a component of the glass skeleton. It is also a solvent that reduces the viscosity of glass melting. Boron oxide triangle [BO3] and boron oxide tetrahedron [BO4] are structural components. Boron may exist in the form of triangle [BO3] or boron oxide tetrahedron [BO4] under different conditions. Under high temperature melting conditions, it is generally difficult to form boron oxide tetrahedron, and it can only exist in the form of trihedron. However, at low temperature, under certain conditions, B 3+ It has a tendency to capture free oxygen to form tetrahedrons, making the structure compact and increasing the low-temperature viscosity of the glass. However, due to its characteristics of reducing the viscosity of the glass at high temperatures and increasing the viscosity of the glass at low temperatures, it is also the main component that reduces the refractive index of the glass, which determines that its content range is relatively small. The preferred weight percentage of the boric acid raw material in the core rod glass is 20-30%. When the content of the boric acid raw material is less than 20%, it cannot play a dissolving role and will also reduce the chemical stability of the glass; when the content of the boric acid raw material is greater than 30%, the refractive index of the glass will be reduced and the phase separation tendency of the glass will also increase.
[0033] La2O3 is introduced as lanthanum oxide, which is a lanthanum series rare earth oxide and can increase the refractive index of glass. The weight percentage of lanthanum oxide is preferably 19.5-30%, but when the lanthanum oxide content is greater than 30%, the thermal expansion coefficient of the glass will increase.
[0034] ZnO is introduced as zinc oxide, with a high bandgap and excitation binding energy, and a high absorption coefficient under certain rays. A small amount of introduction can improve the radiation resistance of glass. The weight percentage of zinc oxide is 1.1-10%. When the content of ZnO is greater than 10%, it will reduce the chemical resistance and thermal expansion coefficient of the glass and increase the tendency of crystallization.
[0035] Nb2O5 is introduced as niobium oxide, which is also a rare earth oxide. It can increase the refractive index of glass and replace part of La2O3. According to the particle hybridization theory, the introduction of multiple particles can improve the stability of the glass structure. The weight percentage of niobium oxide is 1.1-10%, but when the niobium oxide content is greater than 10%, the density and thermal expansion coefficient of the glass will increase.
[0036] BaO is introduced in the form of barium carbonate, which is an external oxide of the glass structure network. It has a high absorption coefficient under certain rays and can improve the radiation resistance of the glass. The weight percentage of the barium carbonate raw material is preferably 10.1-20%. The content of the barium carbonate raw material is greater than 20%, which will increase the crystallization temperature of the glass and increase the crystallization tendency of the glass.
[0037] HfO2 is introduced as hafnium oxide. HfO2 has a wide transparent range from ultraviolet (UV) to infrared (IR), which makes the glass have a good light transmittance foundation in the ultraviolet band and allows ultraviolet light to pass through the glass more easily. The weight percentage of hafnium oxide is 0-3%, but when the hafnium oxide content is greater than 3%, the chemical balance of the glass will be destroyed and the glass will be prone to crystallization.
[0038] Ta2O5 is introduced as tantalum oxide, which is also a rare earth oxide. It can increase the refractive index of glass and replace part of La2O3. According to the particle hybridization theory, the introduction of multiple particles can improve the stability of the glass structure. The weight percentage of tantalum oxide is 5.1-10%, but when the tantalum oxide content is greater than 10%, the density and thermal expansion coefficient of the glass will increase.
[0039] Y2O3 is introduced as yttrium oxide, which is also a rare earth oxide. It can increase the refractive index of glass and replace part of La2O3. According to the particle hybridization theory, the introduction of multiple particles can improve the stability of the glass structure. The weight percentage of yttrium oxide is 1.1-7%, but when the yttrium oxide content is greater than 7%, the density and thermal expansion coefficient of the glass will increase.
[0040] SrO is introduced in the form of strontium carbonate, which is an alkaline earth metal oxide and an external oxide of the glass structure network. It has a high absorption coefficient under certain rays and can improve the radiation resistance of the glass. The weight percentage of the strontium carbonate raw material is preferably 0-5%. When the content of the strontium carbonate raw material is greater than 5%, the chemical stability of the glass will be reduced and the thermal expansion coefficient of the glass will be increased.
[0041] Al2O3 is introduced as aluminum oxide, which is an intermediate oxide of glass. It can improve the radiation resistance of glass and reduce the phase separation tendency of glass. 3+ Prioritizes the formation of free oxygen [AlO4], which enters the glass network. 3+ Occupy Si 4+ Due to Al 3+ and Si 4+ There are different valence states, which require alkali metal ions to fill and balance the valence state. The broken structural chains in the glass are linked again, the structure of the glass tends to be compact, the number of non-bridging oxygen is reduced, and the radiation resistance of the glass is improved. Therefore, within a certain content range, it can become the main body of glass network formation like SiO2. The weight percentage of aluminum oxide is 0.5-7%. When the content of aluminum oxide is greater than 7%, the high-temperature viscosity of the glass will be significantly increased, and the melting temperature of the glass will be increased.
[0042] Na2O is introduced in the form of sodium carbonate, which is an alkali metal oxide and an external oxide of the glass structure network. Na2O repairs the breakpoint between [SiO4] and [BO3], transforms the [BO3] triangular layered structure into a [BO4] tetrahedron, strengthens the network connection, increases the number of bridging oxygen, and moves the ultraviolet intrinsic absorption to the short-wave direction, thereby improving the wide-spectrum transmittance of the glass. The weight percentage of the sodium carbonate raw material is preferably 0-5%. When the content of the sodium carbonate raw material is greater than 5%, the refractive index and thermal expansion coefficient of the glass will increase, and the crystallization tendency of the glass will increase.
[0043] CeO2 is introduced with cerium oxide, which is a rare earth oxide. Cerium is a variable valence element and is in a high valence state under irradiation. 4+ It can first absorb high-energy electrons or free electrons caused by radiation, causing the valence state of the ions to change without causing the establishment of color centers, thereby playing a role in radiation resistance. However, after the valence of the cerium element changes, the element absorbs ultraviolet and visible light in the new valence state, which will also cause the transmittance of the optical fiber imaging array to decrease. 4+ It has strong absorption in the visible light region and is converted into Ce 3+ When the absorption in the spectral region above 300nm is very small. The appropriate amount of Ce element introduced, through the oxygen-enriched melting process, accurately controls the element valence state, so that the amount of cerium introduced can be minimized under the premise that the radiation resistance meets the requirements, thereby resolving the contradiction between ultraviolet transparency (no valence element in the composition as much as possible) and radiation resistance (introducing cerium, a valence element, into the composition to absorb high-energy electrons generated after high-energy radiation to avoid the formation of color centers), achieving radiation resistance while ensuring that the glass has a high transmittance in the ultraviolet region. The weight percentage of cerium oxide is 0.05-2%. When the content of cerium oxide is greater than 2%, the crystallization tendency of the glass will increase and the transmittance of the glass will also be reduced.
[0044] In some specific embodiments of the present invention, the leather tube mixture includes, by mass percentage, 60-75% quartz sand, 1.5-15% boric acid, 1-5% aluminum oxide, 1-10% sodium carbonate, 1-8% potassium bifluoride, 1-8% calcium fluoride, 0-5% basic magnesium carbonate, 0-8% lithium carbonate, 0-5% zinc oxide, 0-2% cerium oxide, wherein the total content of impurities Fe, Cu and Mn is ≤3ppm; the total content of impurities Nd, Pr, U, Er, Eu, Tb, Dy is ≤2ppm. The leather tube mixture is melted, clarified, stirred, molded, and annealed to obtain a leather tube; each component in the leather tube exists in the form of oxides, that is, it contains SiO2, B2O3, Al2O3, Na2O, K2O, CaO, MgO, Li2O, ZnO, and CeO2.
[0045] In the above-mentioned leather tube glass, SiO2 is introduced in the form of quartz sand, which is the main body of the glass skeleton and the main component in the glass skeleton. In the leather tube glass, the weight percentage of quartz sand is 60-75%. When the content of quartz sand raw material is lower than 60%, it is difficult to obtain low refractive index glass, and the chemical resistance stability of the glass will also be reduced; when the content of quartz sand raw material is higher than 75%, the high temperature viscosity of the glass will increase, resulting in excessively high glass melting temperature, and the thermal expansion coefficient of the glass will also be reduced.
[0046] B2O3 is introduced in the form of boric acid, which is an oxide for glass formation and also a component of the glass skeleton. It is also a solvent that reduces the viscosity of glass melting. Boron oxide triangle [BO3] and boron oxide tetrahedron [BO4] are structural components. Boron may exist in the form of triangle [BO3] or boron oxide tetrahedron [BO4] under different conditions. Under high temperature melting conditions, it is generally difficult to form boron oxide tetrahedron, and it can only exist in the form of trihedron. However, at low temperature, under certain conditions, B 3+ It has a tendency to capture free oxygen to form tetrahedrons, making the structure compact and increasing the low-temperature viscosity of the glass. However, due to its characteristics of reducing the viscosity of the glass at high temperatures and increasing the viscosity of the glass at low temperatures, it is also the main component that reduces the refractive index of the glass, which determines that its content range is relatively small. The preferred weight percentage of the boric acid raw material in the leather tube glass is 1.5-15. When the content of the boric acid raw material is greater than 15%, the refractive index of the glass will be reduced, and the phase separation tendency of the glass will also be increased.
[0047] Al2O3 is introduced as aluminum oxide, which is an intermediate oxide of glass. It can improve the radiation resistance of glass and reduce the phase separation tendency of glass. 3+ Prioritizes the formation of free oxygen [AlO4], which enters the glass network. 3+ Occupy Si 4+ Due to Al 3+ and Si 4+ There are different valence states, which require alkali metal ions to fill and balance the valence state. The broken structural chains in the glass are linked again, the structure of the glass tends to be compact, the number of non-bridging oxygen is reduced, and the radiation resistance of the glass is improved. Therefore, within a certain content range, it can become the main body of glass network formation like SiO2. The weight percentage of aluminum oxide is 1-5%. When the content of aluminum oxide is greater than 5%, the high-temperature viscosity of the glass will be significantly increased, and the melting temperature of the glass will be increased.
[0048] Na2O is introduced in the form of sodium carbonate, which is an alkali metal oxide and an external oxide of the glass structure network. Na2O repairs the breakpoint between [SiO4] and [BO3], transforms the [BO3] triangular layered structure into a [BO4] tetrahedron, strengthens the network connection, increases the number of bridging oxygen, and moves the ultraviolet intrinsic absorption to the short-wave direction, thereby improving the wide spectrum transmittance of the glass. The weight percentage of the sodium carbonate raw material is preferably 1-10%. When the raw material content of sodium carbonate is greater than 10%, the refractive index and thermal expansion coefficient of the glass will increase, and the crystallization tendency of the glass will increase.
[0049] K2O is introduced in the form of potassium bifluoride, which is an alkali metal oxide and an external oxide of the glass structure network. K2O repairs the breakpoint between [SiO4] and [BO3], transforms the [BO3] triangular layered structure into a [BO4] tetrahedron, strengthens the network connection, increases the number of bridging oxygen, and moves the ultraviolet intrinsic absorption to the short-wave direction, thereby improving the wide spectrum transmittance of the glass. - The introduction of F can fill the oxygen vacancies in the glass, repair the structural defects and improve the glass transmittance. - The 8-electron structure is stabilized by using its strong binding effect on the outer electrons to reduce the number of high-energy free electrons generated by irradiation, avoid the formation of color centers, and improve the radiation resistance of the glass. The weight percentage of the potassium bifluoride raw material is preferably 1-8%. When the content of the potassium bifluoride raw material is greater than 8%, the refractive index and thermal expansion coefficient of the glass will be increased, and the crystallization tendency of the glass will be increased.
[0050] CaO is introduced in the form of calcium fluoride to improve the radiation resistance and wide spectrum transmittance of the glass. - The introduction of F can fill the oxygen vacancies in the glass, repair the structural defects and improve the glass transmittance. - In order to stabilize the 8-electron structure, the strong binding effect on the outer electrons is utilized to reduce the number of high-energy free electrons generated by irradiation, avoid the formation of color centers, and improve the radiation resistance of the glass. The weight percentage of calcium fluoride raw materials is 1-8%. When the calcium fluoride content is greater than 8%, the chemical stability of the glass will be reduced and the crystallization tendency of the glass will be increased.
[0051] MgO is introduced in the form of basic magnesium carbonate, which is an external oxide of the glass structure network and is used to adjust the crystallization temperature of the glass. The weight percentage of the basic magnesium carbonate raw material is 0-5%. If the content of the basic magnesium carbonate raw material is greater than 5%, the crystallization tendency of the glass will be increased.
[0052] Li2O is introduced in the form of lithium carbonate and is an external oxide in the glass structure network. Lithium oxide has a small ionic radius and high electronegativity, and is easy to enter the glass structure network and exert a greater attraction on the surrounding molecules, which helps to densify the glass structure, reduce internal defects and scattering centers, and thus improve the transmittance of the glass. The weight percentage of lithium carbonate raw materials is 0-8%. When the content of lithium carbonate raw materials is greater than 8%, the expansion coefficient of the glass will be increased.
[0053] ZnO is introduced as zinc oxide, with a high bandgap and excitation binding energy, and a high absorption coefficient under certain radiation exposure. A small amount of introduction can improve the radiation resistance of glass. The weight percentage of zinc oxide is 0-5%. When the zinc oxide content is greater than 5%, the chemical resistance and thermal expansion coefficient of the glass will be reduced, and the tendency of crystallization will be increased.
[0054] CeO2 is introduced with cerium oxide, which is a rare earth oxide. Cerium is a variable valence element and is in a high valence state under irradiation. 4+ It can first absorb high-energy electrons or free electrons caused by radiation, causing the valence state of the ions to change without causing the establishment of color centers, thereby playing a role in radiation resistance. After the cerium element changes its valence, the element absorbs ultraviolet and visible light in the new valence state, which will also cause the transmittance of the optical fiber imaging array to decrease. 4+ It has strong absorption in the visible light region and is converted into Ce 3+ When the absorption in the spectral region above 300nm is very small. The appropriate amount of Ce element introduced, through the oxygen-enriched melting process, accurately controls the valence state of the element, so that the amount of cerium introduced can be minimized under the premise that the radiation resistance meets the requirements, thereby resolving the contradiction between ultraviolet transparency (no valence element in the composition as much as possible) and radiation resistance (introducing cerium, a valence element, into the composition to absorb high-energy electrons generated after high-energy radiation to avoid the formation of color centers), achieving radiation resistance while ensuring that the glass has a high transmittance in the ultraviolet region. The weight percentage of cerium oxide is 0-2%. When the content of cerium oxide is greater than 2%, the crystallization tendency of the glass will increase and the transmittance of the glass will also be reduced.
[0055] In the above steps of preparing the core rod and the leather tube, the purity control of the raw materials is very critical, because the harmful impurities that may exist in the raw materials, such as transition metal valence ions and heavy metal ions, have low electron transition energy, and their electrons absorb energy and undergo transition under high-energy radiation, and have obvious absorption of ultraviolet rays in the ultraviolet region. Therefore, in order to avoid their influence on the transmittance of the glass material in the ultraviolet region, the present invention strictly controls the content of harmful impurities in the oxides or salts used to prepare the core rod and the leather tube. When preparing the mixture, all raw materials are high-purity raw materials, and the content of Fe, Cu, Mn, etc. in the raw materials is strictly controlled, so that the content of coloring elements in all raw materials is controlled below 3ppm; when using rare earth oxides such as Y, La, Ta, Nb, Ce, etc., the introduction of impurity elements such as Nd, Pr, U, Er, Eu, Tb, Dy, etc. is strictly prohibited, and the total content is controlled below 2ppm; thereby ensuring that the glass prepared by this technical solution has excellent comprehensive performance.
[0056] Furthermore, this step requires very high purity of the raw materials, so the containers and tools used in the batching process also need to be strictly controlled. For example, the material of the container for preparing the core rod mixture is strictly controlled to be a non-metallic alkali-resistant material; the material of the container for preparing the leather tube mixture is strictly controlled to be a non-metallic material; if it is a plastic product, it is preferably colorless and transparent; the reason for this arrangement is that: since the container, such as a crucible, will be in direct contact with the glass, whether it is the crucible material or impurities in the crucible, if they are brought into the mixture, they may melt into the glass during the subsequent melting process, which will have an adverse effect on the quality and performance of the glass. For example, if a platinum crucible is used, platinum particles or ions may enter the glass, which will cause ultraviolet absorption to be detrimental to the light transmittance of the glass; in addition On the one hand, depending on the acidity and alkalinity of the glass, if the glass composition does not match the material of the container, the glass composition may cause serious erosion to the container, thereby causing the glass components to be seriously affected and changed, and may even cause leakage of the container due to the erosion of the glass, such as leakage of the crucible, which may be very unfavorable to improving the quality of glass melting; the core rod glass component of the present invention is a silicon-boron-lanthanum-barium system, which is generally alkaline, so it has a heavier erosion effect on quartz crucibles and corundum crucibles. In view of this, the container of the core rod glass of the present invention is preferably no longer a platinum crucible, but a crucible made of magnesium oxide; according to the composition of the leather tube glass in the present invention, a quartz crucible is preferably used, and a high-purity silicon oxide coating is provided on the surface of the crucible, thereby reducing the influence of the crucible component on the glass component and reducing the introduction of impurities.
[0057] In the step of melting the mixture, the mixture can be melted by directly adding the mixture into a container for melting; however, in order to improve the melting efficiency and the quality of the molten glass, the present invention preferably adds the mixture into the melting container in batches during melting; in some specific embodiments of the present invention, the mixture is preferably added into the container in 3-5 times, each time with an interval of 0.5-2 hours; adding the mixture in batches in this way can more efficiently complete the melting of the glass composition.
[0058] The melting process of the glass mixture can be specifically adjusted according to its composition and ingredients. Under the composition formula conditions designed in the technical solution of the present invention, the melting temperature of the core rod mixture is preferably 1450-1520°C, and the melting temperature of the leather tube core rod mixture is preferably 1350-1400°C, so that the glass composition can be melted quickly.
[0059] After the glass mixture is completely melted, the glass liquid can be clarified and stirred. In this step, the clarification and stirring temperature of the core rod glass is preferably 1520-1600°C, and the clarification and stirring temperature time is 1-2h; during the clarification process of the glass liquid, forced stirring is preferably performed throughout the process; the material of the agitator is preferably a non-metallic alkali-resistant material to avoid contact with the glass liquid and the introduction of harmful impurities. The clarification and stirring temperature of the leather tube glass is preferably 1460-1530°C, and the clarification and stirring temperature time is 1-2h; during the clarification process of the glass liquid, stirring is preferably performed throughout the process; the material of the agitator is preferably a non-metallic material to avoid contact with the glass liquid and the introduction of harmful impurities. In the above-mentioned clarification step, it is preferred that the agitator uses a double-blade paddle to improve the stirring effect.
[0060] In order to ensure that the obtained glass can have a high transmittance under irradiation conditions, the present invention strictly limits the introduction of oxygen into the glass melt during the glass melting, clarification and stirring stages so that the glass melt can be in a strong oxidizing atmosphere. The amount of oxygen introduced will adjust the concentration of the oxidizing atmosphere of the glass melt so that the variable valence element can be melted in an oxygen-rich environment, so that the glass melt has a sufficient amount of high-valence variable valence elements to meet the radiation resistance of the glass, and at the same time, the amount of high-valence variable valence elements will not be too high, resulting in the absorption of light by high-valence variable elements and affecting the transmittance of the glass. In some specific embodiments of the present invention, the flow rate of oxygen introduced into the glass melt by the core rod glass is preferably 0.1-0.3 mol / L / min, and the flow rate of oxygen introduced into the glass melt by the leather tube glass is preferably 0.04-0.18 mol / L / min, so that the valence state of the radiation-resistant variable valence element cerium can be accurately adjusted to ensure that the core rod glass has a high transmittance and high radiation resistance under irradiation conditions.
[0061] The melting of glass is generally carried out in an open crucible. Since the decomposition of the raw materials in the glass mixture may produce a large amount of volatilized gas, and some components in the glass composition are also volatile, these volatile components will corrode the materials of the melting furnace, and the corroded materials may also affect the glass itself through the crucible mouth. For this reason, the present invention preferably uses a refractory material as the material of the melting and clarification melting furnace, and strictly controls the content of heavy metals such as lead, cadmium, and mercury to ≤5ppm, thereby directly reducing the adverse effects of the melting furnace material on the quality of the glass liquid; further, by preferably using the refractory material as a corrosion-resistant and high-temperature resistant material, preferably with a temperature resistance of ≥1700°C, it can avoid or reduce the corrosion of the volatile components of the glass on the melting furnace, thereby indirectly reducing the adverse effects of the melting furnace material on the quality of the glass liquid.
[0062] Furthermore, in order to avoid cross-contamination of glass due to erosion of the refractory materials of the melting furnace, the present invention preferably uses a dedicated melting furnace for heating the container, that is, the melting furnace for preparing core rod glass is only used for melting core rod glass of this formula, and the melting furnace for preparing skin tube glass is only used for melting skin tube glass of this formula, thereby avoiding or reducing cross-contamination caused by the melting furnace material; the present invention may further preferably replace it regularly according to usage and erosion conditions, so as to prevent harmful impurities such as Fe and Ti in the refractory material from entering the glass, thereby avoiding or reducing the influence of the melting furnace on the composition of the glass liquid.
[0063] The core rod glass liquid is discharged by injecting the glass liquid into the core rod mold and casting it into the core rod glass of the required specifications; after annealing, the core rod can be obtained. The leather tube glass liquid is discharged by injecting the glass liquid into the leather tube mold and casting it into the leather tube glass of the required specifications; after annealing, the leather tube can be obtained. The temperature and time of the glass liquid discharge, molding and annealing can be adjusted according to the actual composition of the glass composition. In some specific embodiments of the present invention, according to the composition of the glass composition, the discharge temperature of the core rod glass is preferably 1360-1400℃, the annealing temperature is 600-650℃, and the annealing time is 2-4h; the discharge temperature of the leather tube glass is preferably 1300-1350℃, the annealing temperature is 550-600℃, and the annealing time is 2-4h.
[0064] The second step is to put the tube on the core rod and draw the single wire. When the two glasses are nested, the performance matching of the two glasses is very critical. First, if the matching of the two is not good, the fiber interface may be uneven. When the light propagates on these uneven interfaces, scattering will occur, resulting in optical signal loss and reducing the light collection ability of the fiber image transmission array; second, if the thermal expansion coefficients of the core rod glass and the tube glass do not match, the core glass will be subjected to excessive compressive stress or tensile stress during the heat treatment process, which will reduce the strength of the optical fiber and destroy the roundness and structure of the optical fiber; third, if the softening temperatures of the core rod glass and the tube glass do not match, the fiber core will be deformed during the pressing process, and the total reflection conditions will not be met, resulting in light leakage; fourth, if the viscosity of the core rod glass and the tube glass does not match, the softening degree of the two glasses will be inconsistent during the drawing process, which is not conducive to fiber drawing; fifth, if the chemical compatibility of the core rod glass and the tube glass is poor, the glass will permeate each other or crystallize and separate during the plate making process, resulting in an incomplete core-skin interface and a decrease in transmittance. Therefore, in addition to ensuring the high refractive index of the core rod glass and the low refractive index of the skin tube glass, the performance matching of the two glasses is also critical.
[0065] The present invention limits the difference between the thermal expansion coefficient of the core rod glass and the thermal expansion coefficient of the skin tube glass to 1×10 -7 / ℃~10×10 -7 / ℃; through the performance matching design of the core rod glass and the skin tube glass, the thermal expansion coefficients of the core rod glass and the skin tube glass are made similar, which can prevent the optical fiber from bursting due to the mismatch of thermal expansion coefficients during the heating or cooling process of the glass, and on the other hand, in the subsequent optical fiber drawing and heating process, the skin layer can better adhere to the core glass, and in the drawing and cooling process, the skin layer can also produce a certain compressive stress, thereby improving the strength of the optical fiber, ensuring that compressive stress can be formed during the drawing process, and enhancing the strength of the optical fiber yarn; the present invention limits the difference between the softening temperature of the core rod glass and the softening temperature of the skin tube glass to 10-25℃, which can ensure that the core and skin glass in the subsequent drawing process The roundness of the glass is improved, so that the skin material softens and bonds during the pressing process, while the core material can still maintain a circular structure, thereby preventing the transmission light from leaking due to the deformation of the fiber core and failure to meet the total reflection condition; the present invention limits the core rod glass and the skin tube glass to be chemically stable at 810°C, that is, the two glasses will not penetrate, crystallize or separate when kept at 810°C for 5 hours, thereby effectively solving the problem of reduced transmittance caused by incomplete core-skin interface due to mutual penetration or crystallization and phase separation between the glasses during the process; the present invention limits the difference between the refractive index of the core rod glass and the refractive index of the skin tube glass to more than 0.3; thereby effectively improving the optical fiber imaging array light flux N A, which improves the transmission efficiency of the fiber optic imaging array and reduces the loss of images or signals during transmission, thereby improving the overall transmission quality of the fiber optic imaging array.
[0066] The present invention limits the difference between the inner diameter of the leather tube glass and the outer diameter of the core rod glass to 0.4-0.6 mm. The technical purpose of this setting is to make it more conducive for the leather material to be close to the rod material during the wire drawing process and to ensure that a single wire with good roundness and consistent size is drawn; the present invention further preferably sets the difference between the inner diameter of the leather tube glass and the outer diameter of the core rod glass to 0.5 mm.
[0067] In some specific embodiments of the present invention, a high refractive index core glass rod is finely ground and polished to a diameter of 30.0-32.0 mm, and then matched with a low refractive index skin glass tube with a thickness of 3.2-4.2 mm and an inner diameter of 30.5-32.5 mm for single wire drawing. The diameter of the single wire is 3.2-4.0 mm; the length is 450-500 mm; the single wire drawing temperature is 780-800°C, and the rod drawing speed is 1.0-1.5 mm / min.
[0068] The drawing step of the monofilaments also includes the drawing of triangular light-absorbing filaments. The triangular light-absorbing filaments are used to insert into the pores formed by the adjacent monofilaments to ensure the transmission of light in the optical fiber; the light-absorbing filaments are designed as triangular filaments, on the one hand to improve the absorption of light, and on the other hand to help control the loss of light in different directions in the optical fiber, thereby controlling the directionality of light transmission. In some specific embodiments of the present invention, the edges and corners of the triangular light-absorbing filaments are all chamfered structures. This structural design is to avoid or reduce the stress concentration caused by sharp corners, so that the stress distribution is more uniform and the mechanical stability and service life of the optical fiber are improved; on the other hand, the sharp corners may scratch or damage the cladding or core surface inside the optical fiber. The triangular absorption filaments designed as chamfered ones can enter more smoothly during the insertion process of the optical fiber gap, avoiding physical damage to the internal structure of the optical fiber, thereby ensuring that the optical performance of the optical fiber is not damaged. In some specific embodiments of the present invention, a triangular special-shaped light-absorbing glass rod with a chamfered side length of 2.5 to 3.5 mm is drawn into a triangular light-absorbing filament, and the filament diameter of the light-absorbing filament is 0.60 to 0.80 mm.
[0069] The third step is to draw a primary multifilament. In some specific embodiments of the present invention, the monofilaments drawn from the rod tube are arranged into a primary composite rod with a regular hexagonal cross section according to the requirement of 4 to 7 monofilaments on each side, and the triangular light absorbing monofilaments are used as filling wires, and then the filling wires are evenly inserted into the primary composite rod, and the arranged rods are tightly tied; then the primary composite rod is drawn into a primary multifilament, and the hexagonal opposite side size of the primary multifilament is preferably controlled to be 0.9 to 1.5 mm; the primary multifilament drawing temperature is 820 to 840°C, and the rod lowering speed is 1.4 to 2.0 mm / min.
[0070] The fourth step is secondary multifilament drawing. In some specific embodiments of the present invention, the drawn primary multifilaments are arranged into a secondary composite rod with a cross section of a regular hexagonal square according to the requirement of 15 to 19 strands per side, and are drawn into secondary multifilaments by a high-precision lossless wire drawing machine to avoid friction and damage of the optical fiber caused by contact with the roller. The hexagonal opposite side size of the secondary multifilament is preferably controlled to be 0.9 to 1.3 mm; the secondary multifilament drawing temperature is 810 to 820°C, and the rod lowering speed is 1.0 to 1.5 mm / min.
[0071] In some specific embodiments of the present invention, the secondary multifilaments are cut into secondary multifilament segments with a length of 132 to 137 mm, and then arranged in a hexagonal and closely packed manner according to the requirement of 30 to 36 secondary multifilament segments on each side to avoid the occurrence of internal structural defects.
[0072] In order to eliminate the surface contamination of the secondary multifilaments and promote the densification of the leather surface, the present invention uses a high vacuum fiber surface cleaning device to clean the surface of the secondary composite fiber. At this temperature, the fiber surface activity is relatively large, and the glass on the fiber surface has no fluidity. In some specific embodiments of the present invention, the process is as follows: first, the secondary multifilament fibers are precisely arranged in a precisely shaped glass tube, and the glass tube is evacuated to 10 by a pump. -6 Pa, the temperature is raised to 450-480°C, and then oxygen is introduced to treat the secondary multifilament fiber. After 20-30 minutes, the oxygen is extracted. The steps of introducing oxygen, keeping the temperature and extracting oxygen are carried out in sequence, and repeated 2-3 times to ensure that the pollutants on the fiber surface are ablated cleanly and the oxygen vacancies in the fiber surface structure are repaired. Then, the vacuum is evacuated to 10 -6 Pa, to ensure that the fiber surface is clean and dense. After cleaning, the glass tube is sealed under high vacuum.
[0073] Preferably, during fiber cleaning, after oxygen has completed ablating pollutants and repairing oxygen vacancies, and after oxygen is extracted, a step of introducing helium into the glass tube to replace the oxygen is also included. Helium is an inert gas with very stable chemical properties and is not easy to react chemically with fibers. The introduction of helium can replace the oxygen and other gases remaining in the reaction system, thereby preventing unnecessary secondary reactions between the residual oxygen and the fibers during subsequent cooling or other operations, thereby affecting the treated fiber surface and protecting the fibers. In the process of repeatedly introducing helium, the helium gas flow can carry away some tiny particles or volatile impurities that may be produced during the oxygen ablation process, further ensuring the cleanliness of the fiber surface.
[0074] The sixth step is gas melt pressing. In order to eliminate the uneven force on the fibers during the mechanical forming process, the uneven elongation of the fibers during the hot pressing process, the uneven fiber structure of the optical fiber imaging array, and the microstructural defects of the optical fiber imaging array, the present invention preferably adopts isostatic pressing technology to achieve blank melt pressing. In some specific embodiments of the present invention, the fiber after surface cleaning sealed under a high vacuum state is placed in a gas melt pressing mold as a whole, at 600-650°C, the isostatic pressing time is 20-40min, the cylinder is gradually pressurized and filled with nitrogen, the nitrogen pressure is 10-13MPa, and the plate is pressed according to the designed compression ratio before and after the gas melt pressing of the plate segment, and after gas melt pressing, a fiber optic imaging array blank plate segment with a unit wire diameter of 3-6μm is produced.
[0075] Finally, the prepared blank plate segment is processed into a fiber optic image transmission array through rounding, cutting, and end surface grinding and polishing. The operation of this step can be performed according to conventional operations in the art, and the present invention does not specifically limit this.
[0076] The present invention, through the definition of the above technical solution, can obtain a fiber optic imaging array with wide spectrum response and radiation resistance.
[0077] The present invention also proposes a wide spectrum response radiation-resistant optical fiber imaging array, whose unit fiber diameter is 3 to 6 μm; the optical fiber imaging array has a spectral transmittance of ≥60% in the wavelength range of 330-2000 nm at a thickness of 100 mm; after irradiation for 500 h at a 6.4 kGy irradiation dose, the transmittance attenuation rate at 350 nm is ≤5%; it has excellent fixed pattern noise performance; and there is no obvious multifilament boundary when observed under a 10x microscope.
[0078] The present invention also proposes an application of the wide spectrum response radiation-resistant optical fiber image transmission array described above in wide spectrum detection in high-radiation environments in the aerospace field.
[0079] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0080] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0081] 1. Preparation of core rod glass:
[0082] Raw material requirements: quartz sand (4N, 160μm sieve oversize is less than 5%, 40μm sieve undersize is less than 5%), boric acid (analytical grade, 400μm sieve oversize is less than 10%, 63μm sieve undersize is less than 10%), strontium carbonate (analytical grade, purity ≥99.0%), lanthanum oxide (5N), niobium oxide (5N), yttrium oxide (5N), tantalum oxide (5N), zinc oxide (analytical grade), aluminum oxide (analytical grade, average particle size 50μm), sodium carbonate (analytical grade), barium carbonate (analytical grade), hafnium oxide (analytical grade), cerium oxide (4N), impurities in high-purity reagent raw materials are strictly controlled to have a total content of coloring elements such as Fe, Cu, and Mn <3ppm; when using rare earth oxides such as Y, La, Ta, and Nb, the introduction of impurity elements such as Nd, Pr, U, Er, Eu, Tb, and Dy is strictly prohibited, and the total content is controlled to be <2ppm.
[0083] Example 1-1
[0084] Melting of core rod glass: Select raw materials according to the glass composition of Example 1-1 in Table 1-1, weigh the raw materials according to the ingredient list, mix them evenly and put them into a magnesium oxide crucible. The containers and utensils used in the batching and material processing are all made of non-metallic materials, and the plastic products are colorless and transparent. The content of lead, cadmium and mercury in the refractory material of the furnace top is controlled below 5ppm, and it is resistant to corrosion and high temperature above 1700℃. The melting electric furnace must be dedicated to avoid cross contamination caused by erosion of the refractory material. It should be replaced regularly according to the use and corrosion conditions to prevent harmful impurities such as Fe and Ti in the refractory material from entering the glass.
[0085] The mixture is added to the crucible 4 times every 1 hour for high temperature melting at 1500℃. After the raw material mixture is melted, it is clarified and stirred at a temperature of 1550℃ for 1.5 hours. The stirrer adopts a double-blade paddle to improve the stirring effect. During this melting and clarification stage, the oxygen valve is opened to introduce oxygen into the glass liquid at a flow rate of 0.2mol / L / min to make the glass liquid present a strong oxidizing atmosphere. The molten and clarified glass liquid is discharged at 1370℃ and cast into the required glass in a mold. After the glass is cooled and solidified, it is annealed at an annealing temperature of 640℃ and a heat preservation time of 2.5 hours to obtain the core rod glass of the present invention.
[0086] After testing, the core rod glass prepared in this embodiment has a spectral transmittance of 67% in the wavelength range of 330-2000nm at a thickness of 100mm; a transmittance attenuation rate of 2.6% at 350nm after irradiation for 500h at a dose of 6.4kGy; a refractive index of 1.8023; and an average linear thermal expansion coefficient of 91.0×10 -7 / ℃; kept at 810℃ for 5 hours without crystallization.
[0087] Example 1-2 to Example 1-5
[0088] The process is the same as that of Example 1-1. The core rod glass composition formula, raw material purity and process parameters are shown in Table 1. The test results are also shown in Table 1.
[0089] Table 1 Chemical composition, process parameters and properties of core rod glass of Examples 1-1 to 1-5
[0090]
[0091]
[0092] Note: a′ represents the total content of Fe, Cu, Mn and other coloring elements in high-purity reagent quartz sand, lanthanum oxide, niobium oxide, yttrium oxide, tantalum oxide and cerium oxide, in ppm; b′ represents the total content of Nd, Pr, U, Er, Eu, Tb and Dy impurities in rare earth oxides of lanthanum oxide, niobium oxide, yttrium oxide, tantalum oxide and cerium oxide, in ppm; c′ represents the spectral transmittance of 330nm~2000nm, in %; d′ represents the transmittance attenuation rate (irradiated for 500h at 6.4kGy irradiation dose, at 350nm), in %; e′ represents the refractive index; f′ represents the average linear thermal expansion coefficient in the range of 30~300℃, in ×10 -7 / ℃.
[0093] 2. Preparation of leather tube glass:
[0094] Raw material requirements: quartz sand (4N, 160μm sieve material is less than 5%, 40μm sieve material is less than 5%), boric acid (analytical grade, 400μm sieve material is less than 10%, 63μm sieve material is less than 10%), zinc oxide (analytical grade), aluminum oxide (analytical grade, average particle size 50μm), sodium carbonate (analytical grade), potassium bifluoride (analytical grade), calcium fluoride (analytical grade), basic magnesium carbonate (chemically pure, average particle size 50μm), lithium carbonate (analytical grade), cerium oxide (4N). The total content of Fe, Cu, and Mn coloring elements in high-purity raw materials is strictly controlled to be less than 3ppm. When rare earth cerium oxide is used, the introduction of impurity elements such as Nd, Pr, U, Er, Eu, Tb, and Dy is strictly prohibited, and the total content is controlled to be less than 2ppm.
[0095] Example 2-1
[0096] Melting of leather tube glass: Select raw materials according to the glass composition of Example 2-1 in Table 2, weigh the raw materials according to the ingredient list, mix them evenly and put them into a quartz crucible with a high-purity silicon oxide coating on the surface. The containers and utensils used in the batching and chemical process are all made of non-metallic materials, and the plastic products are colorless and transparent. The content of lead, cadmium and mercury in the refractory material of the furnace top is controlled below 5ppm, and it is resistant to corrosion and high temperature above 1700℃. The smelting electric furnace must be dedicated to avoid cross contamination caused by erosion of the refractory material. It should be replaced regularly according to the use and corrosion conditions to prevent harmful impurities such as Fe and Ti in the refractory material from entering the glass.
[0097] The mixture is added to the crucible 5 times at intervals of 0.5 hours for high temperature melting at 1360°C. After the raw material mixture is melted, it is clarified and stirred at a temperature of 1470°C for 2 hours. The stirrer adopts a double-blade paddle to improve the stirring effect. During this melting and clarification stage, the oxygen valve is opened to introduce oxygen into the glass liquid at a flow rate of 0.044 mol / L / min to make the glass liquid present a strong oxidizing atmosphere. The molten and clarified glass liquid is discharged at 1300°C and cast into the required glass in a mold. After the glass is cooled and solidified, it is annealed at an annealing temperature of 550°C and a heat preservation time of 4 hours to obtain the leather tube glass of the present invention.
[0098] After testing, the leather tube glass prepared in this embodiment has a spectral transmittance of 75.8% in the wavelength range of 330-2000nm at a thickness of 100mm; a transmittance attenuation rate of 2.3% at 350nm after irradiation for 500h at a dose of 6.4kGy; a refractive index of 1.4985; and an average linear thermal expansion coefficient of 82×10 -7 / ℃; kept at 910℃ for 5 hours without crystallization.
[0099] Example 2-2 to Example 2-5
[0100] The process is the same as that of Example 2-1. The formula of the leather tube glass composition, the purity of the raw materials and the process parameters are shown in Table 2, and the test results are also shown in Table 2.
[0101] Table 2 Chemical composition, process parameters and properties of leather tube glass of Examples 2-1 to 2-5
[0102]
[0103]
[0104] Note: a represents the total content of Fe, Cu, Mn and other coloring elements in high-purity reagent quartz sand and cerium oxide, in ppm; b represents the total content of Nd, Pr, U, Er, Eu, Tb, Dy impurities in cerium oxide, in ppm; c represents the spectral transmittance of 330nm~2000nm, in %; d represents the transmittance attenuation rate (irradiated for 500h at 6.4kGy irradiation dose, at 350nm), in %; e represents the refractive index; f represents the average linear thermal expansion coefficient in the range of 30~300℃, in ×10 -7 / ℃.
[0105] 3. Preparation of Fiber Optic Image Transmission Array
[0106] Example 3-1
[0107] The core rod prepared in Example 1-1 and the leather tube prepared in Example 2-1 were nested and used to prepare a fiber optic imaging array. The process parameters and results are shown in Table 3.
[0108] The specific steps are as follows:
[0109] 1) Single wire drawing: core rod glass and skin tube glass were prepared according to the corresponding examples in Table 1 and Table 2. The surface of the core glass rod was finely ground and polished to a diameter of 30.0 mm, and then a skin glass tube with a thickness of 3.2 mm and an inner diameter of 30.5 mm was combined to perform single wire drawing; the prepared single wire had a diameter of 3.2 mm; the single wire drawing temperature was 780°C, and the rod lowering speed was 1.0 mm / min.
[0110] 2) Drawing of triangular light absorbing wire: a triangular shaped light absorbing glass rod with a length of 470 mm and a chamfered side length of 2.5 mm is drawn into a triangular light absorbing wire, and the wire diameter of the light absorbing wire is controlled to be 0.61 mm;
[0111] 3) Drawing of primary multifilament: Arrange the monofilaments into a primary composite rod with a regular hexagonal cross section according to the requirement of 6 monofilaments on each side, insert the triangular light absorbing monofilaments as filling wires evenly into the primary composite rod, and tie the rods; then draw the primary composite rod into a primary multifilament, and control the hexagonal opposite side size of the primary multifilament to be 0.9mm; the primary multifilament drawing temperature is 820℃, and the rod drawing speed is 1.4mm / min;
[0112] 4) Secondary multifilament drawing: Arrange the primary multifilament into a secondary composite rod with a hexagonal cross section according to the requirement of 19 strands on each side, and use a high-precision lossless wire drawing machine to draw the secondary multifilament, and control the hexagonal opposite side size of the secondary multifilament to be 0.9mm; the secondary multifilament drawing temperature is 810℃, and the rod drawing speed is 1.2mm / min;
[0113] 5) Arrangement: Cut the secondary multifilament into 137 mm long segments, and then arrange them into a hexagonal close-packed pattern with 36 segments on each side. The specific arrangement steps are as follows: First, precisely arrange the secondary multifilament fibers into a precisely shaped glass tube, and evacuate the glass tube to 10 -6 Pa, heat to 450℃, then introduce oxygen to treat the fiber, keep warm for 20 minutes, extract oxygen; introduce oxygen again, keep warm, evacuate, repeat cleaning 3 times; then introduce helium into the glass tube for oxygen replacement and purge, then extract helium, evacuate the glass tube to 10 -6 Pa, close the glass tube;
[0114] 6) Gas melting and pressing: the surface-cleaned secondary multifilament fiber sealed under high vacuum is placed in a gas melting and pressing mold as a whole, and the isostatic pressing time is 40 min at 600°C. Nitrogen is gradually pressurized and filled into the cylinder body, and the nitrogen pressure is 13 MPa. The plate is pressed according to the designed compression ratio before and after the gas melting and pressing of the plate segment, and the optical fiber image transmission array blank plate segment with a unit wire diameter of 3.2 μm is produced after the gas melting and pressing;
[0115] 7) Finishing: The prepared fiber optic imaging array blank plate segment is processed into a 3.2 μm fiber optic imaging array through rounding, cutting, and end surface grinding and polishing.
[0116] The unit fiber diameter of the wide spectral response radiation-resistant optical fiber imaging array prepared in this embodiment is 3.2μm. The optical fiber imaging array has a spectral transmittance of 61% in the wavelength range of 330-2000nm at a thickness of 100mm, and a transmittance attenuation rate of 4.2% at 350nm after irradiation for 500h at a 6.4kGy irradiation dose. It has excellent fixed pattern noise performance and no obvious multifilament boundary when observed under a 10x microscope.
[0117] Examples 3-2 to 3-5
[0118] Same as Example 3-1, the differences and results are shown in Table 3.
[0119] Comparative Example 1
[0120] The same as Example 3-1, except that the secondary multifilament was not placed in the glass tube for cleaning during arrangement; the results are as follows: the prepared optical fiber imaging array has a spectral transmittance of 56% in the wavelength range of 330-2000nm at a thickness of 100mm, and a transmittance attenuation rate of 8% at 350nm after irradiation for 500h at a dose of 6.4kGy.
[0121] Comparative Example 2
[0122] The same as Example 3-1, except that the conventional hot melt pressing process was adopted instead of gas melting pressing; the results are as follows: the prepared optical fiber imaging array has a spectral transmittance of 55% in the wavelength range of 330-2000nm at a thickness of 100mm, and a transmittance attenuation rate of 9% at 350nm after irradiation for 500h at a irradiation dose of 6.4kGy.
[0123] Table 3 Process parameters and results of Examples 3-1 to 3-5
[0124]
[0125]
[0126] It can be seen from the test data shown in Table 1 that the core rod glass prepared in the embodiment of the present invention has excellent comprehensive performance, which meets the requirements of wide spectrum response, radiation resistance and high refractive index at the same time, and has a high transmittance in the ultraviolet region. It can be seen from the test data shown in Table 2 that the leather tube glass prepared in the embodiment of the present invention has excellent comprehensive performance, which meets the requirements of wide spectrum response, radiation resistance and low refractive index at the same time, and has a high transmittance in the ultraviolet region. It can be seen from the test data shown in Table 3 that the optical fiber image transmission array prepared by the method of the present invention has excellent comprehensive performance, and its unit fiber diameter is 3 to 6 μm, and at a thickness of 100 mm, the spectral transmittance is ≥60% in the wavelength range of 330-2000 nm; irradiated for 500 h at a 6.4 kGy irradiation dose, the transmittance attenuation rate at 350 nm is ≤5%; and it has excellent fixed pattern noise performance, and there is no obvious multifilament boundary when observed under a 10x microscope, which can meet the requirements of long-distance detection and long service life in ray irradiation environments such as the aerospace field. In comparative example 1, the secondary multifilament fiber was not cleaned during the plate arrangement process, and during the fiber forming process, the fiber surface had to contact the traction wheel for many times, and during the arrangement process, the fiber arrangement operations such as the rod arrangement and the plate arrangement were all manual operations, which easily caused damage to the fiber surface; at the same time, some equipment contact and dust, moisture, CO2, etc. in the air will cause pollution to the fiber surface; especially in the secondary composite fiber stage, the fiber cortex thickness is small and the surface energy is very large, which will aggravate the accumulation of these pollutants on the fiber surface; these pollutants enter the fiber structure, on the one hand, it will affect the light transmission performance of the fiber, especially in the melt-pressing process, these pollutants and damage will cause new structural defects, and it is easy to form color centers under high-energy ray irradiation conditions, resulting in a decrease in the radiation resistance of the optical fiber image transmission array. In comparative example 2, a conventional hot melt pressing process was used. Due to reasons such as mold accuracy and uneven temperature field, the fiber was subjected to uneven force, causing unexpected deformation of the fiber, resulting in uneven fiber elongation, resulting in uneven internal structure of the optical fiber image transmission array, thereby generating microstructural defects, resulting in a decrease in the transmittance and radiation resistance of the optical fiber image transmission array.
[0127] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.
[0128] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a wide spectral response radiation-resistant optical fiber image transmission array, characterized in that: It includes the following steps: S11: putting a leather tube on a core rod to draw a single wire; arranging the single wire into a rod, drawing a multi-filament twice to obtain a secondary multi-filament; at a thickness of 100 mm, in a wavelength range of 330 to 2000 nm, the spectral transmittance of the core rod glass is ≥65%, and the spectral transmittance of the leather tube glass is ≥75%; irradiating for 500 hours at a 6.4 kGy irradiation dose, at 350 nm, the transmittance attenuation rate of the core rod glass and the leather tube glass is ≤3%; the refractive index of the core rod glass is ≥1.8; the refractive index of the leather tube glass is ≤1.5; S12: arranging the secondary multifilaments in a precisely shaped glass tube and heating them under vacuum; introducing oxygen into the glass tube to clean the secondary multifilaments; and then sealing the glass tube under vacuum; S13: placing the sealed glass tube in a gas melting and pressing mold, and isostatically pressing the mold under heating conditions to obtain a fiber optic imaging array blank; S14 performs fine processing on the blank to obtain a wide spectral response radiation-resistant optical fiber image transmission array.
2. The preparation method according to claim 1, characterized in that: The difference between the thermal expansion coefficient of the core rod glass and the thermal expansion coefficient of the tube glass is 1×10 -7 / ℃~10×10 -7 / ℃; the softening temperature of the core rod glass minus the softening temperature of the skin tube glass is 10~25℃; the refractive index of the core rod glass minus the refractive index of the skin tube glass is greater than 0.3; both the core rod glass and the skin tube glass remain chemically stable at 810℃; the inner diameter of the skin tube glass minus the outer diameter of the core rod glass is 0.4~0.6mm.
3. The preparation method according to claim 1, characterized in that: The heating control temperature in step S12 is 450-480°C; the cleaning is carried out under vacuum pressure ≤10 -6 Pa, oxygen is introduced into the glass tube, the temperature is kept, and then the oxygen is extracted; the cleaning times are 2 to 3 times; after cleaning, helium is introduced into the glass tube for replacement, and then the helium is extracted and vacuumized to make the vacuum pressure of the glass tube ≤10 -6 Pa.
4. The preparation method according to claim 1, characterized in that: The heating control temperature in step S13 is 600-650° C.; the isostatic pressing is carried out in a nitrogen atmosphere of 10-13 MPa for 20-40 minutes.
5. The preparation method according to claim 1, characterized in that: When the primary multifilament rods are arranged, triangular light absorbing wires are inserted into the gaps of the primary multifilaments; the edges and corners of the triangular light absorbing wires are all chamfered structures; the secondary multifilaments are drawn using a high-precision lossless wire drawing machine.
6. The preparation method according to claim 1, characterized in that: The preparation method of the mandrel and the leather tube is as follows: S61 raw materials are measured and mixed to obtain a core rod mixture and a leather tube mixture; S62 melts the core rod mixture and the skin tube mixture respectively, clarifies and stirs, discharges, casts and anneals to obtain the core rod or skin tube; the core rod mixture comprises, by weight percentage, 10-15% quartz sand, 20-30% boric acid, 19.5-30% lanthanum oxide, 1.1-10% zinc oxide, 1.1-10% niobium oxide, 10.1-20% barium carbonate, 0-3% hafnium oxide, 5.1-10% tantalum oxide, 1.1-7% yttrium oxide, 0-5% strontium carbonate, 0.5-7% aluminum oxide, 0-5% sodium carbonate and 0.05-2% cerium oxide; the skin tube mixture comprises, by weight percentage, 60-75% quartz sand, 1.5-15% boric acid, 19.5-30% lanthanum oxide, 1.1-10% zinc oxide, 1.1-10% niobium oxide, 10.1-20% barium carbonate, 0-3% hafnium oxide, 5.1-10% tantalum oxide, 1.1-7% yttrium oxide, 0-5% strontium carbonate, 0.5-7% aluminum oxide, 0-5% sodium carbonate and 0.05-2% cerium oxide. Aluminum 1-5%, sodium carbonate 1-10%, potassium bifluoride 1-8%, calcium fluoride 1-8%, basic magnesium carbonate 0-5%, lithium carbonate 0-8%, zinc oxide 0-5%, cerium oxide 0-2%; in the two mixtures, the total content of impurities Fe, Cu and Mn is ≤3ppm; the total content of impurities Nd, Pr, U, Er, Eu, Tb, Dy is ≤2ppm; the instruments for preparing and melting the core rod mixture are all made of non-metallic alkali-resistant materials; the instruments for preparing and melting the leather tube mixture are all made of non-metallic materials; oxygen is introduced into the glass liquid during the melting, clarifying and stirring steps; the material of the melting furnace used for melting and clarifying is refractory material, and its heavy metal content is ≤5ppm.
7. The preparation method according to claim 6, characterized in that: The container for melting the core rod mixture is a crucible made of magnesium oxide; the container for melting the tube mixture is a crucible made of quartz, and the surface of the crucible is provided with a silicon oxide coating; the refractory material is a corrosion-resistant and high-temperature resistant material, and its temperature resistance is ≥1700°C; the melting furnace for melting the core rod mixture is dedicated to the preparation of the core rod glass; or, the melting furnace for melting the tube mixture is dedicated to the preparation of the tube glass.
8. The preparation method according to claim 6, characterized in that: When preparing the core rod, the flow rate of oxygen introduced into the glass liquid is 0.1-0.3 mol / L / min; or, when preparing the leather tube, the flow rate of oxygen introduced into the glass liquid is 0.04-0.18 mol / L / min.
9. A wide spectral response radiation-resistant optical fiber image transmission array, characterized in that: The unit fiber diameter is 3-6 μm; the optical fiber imaging array has a spectral transmittance of ≥60% in the wavelength range of 330-2000 nm at a thickness of 100 mm; the transmittance attenuation rate at 350 nm is ≤5% after irradiation for 500 h at a 6.4 kGy irradiation dose; and no obvious multifilament boundary is observed under a 10x microscope.
10. Application of the wide spectrum response radiation-resistant optical fiber image transmission array according to claim 9 in wide spectrum detection in high radiation environment in the aerospace field.
Citation Information
Cited By
Graded refractive index optical fiber image transmission array and preparation method and application thereof
CN121578439A
Tapered fiber array with designed fiber transmission trajectories, preparation device, preparation method and optoelectronic imaging device containing same
CN122710260A